2017
DOI: 10.1038/srep43959
|View full text |Cite
|
Sign up to set email alerts
|

Locus-specific Retention Predictor (LsRP): A Peptide Retention Time Predictor Developed for Precision Proteomics

Abstract: The precision prediction of peptide retention time (RT) plays an increasingly important role in liquid chromatography–tandem mass spectrometry (LC–MS/MS) based proteomics. Owing to the high reproducibility of liquid chromatography, RT prediction provides promising information for both identification and quantification experiment design. In this work, we present a Locus-specific Retention Predictor (LsRP) for precise prediction of peptide RT, which is based on amino acid locus information and Support Vector Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…These features predict the relative hydrophobicity of peptide sequences and thus RTs for LC used with MS [24][25][26][27][28][29][30]. The predicted RTs can be improved by implementing machine learning algorithms that incorporate confident, observed peptides as training data [14,18,[31][32][33][34]. Predicted peptide RTs are mostly used for scheduling targeted MS/MS analyses where acquisition time is limited, e.g., multiple reaction monitoring [21].…”
Section: Introductionmentioning
confidence: 99%
“…These features predict the relative hydrophobicity of peptide sequences and thus RTs for LC used with MS [24][25][26][27][28][29][30]. The predicted RTs can be improved by implementing machine learning algorithms that incorporate confident, observed peptides as training data [14,18,[31][32][33][34]. Predicted peptide RTs are mostly used for scheduling targeted MS/MS analyses where acquisition time is limited, e.g., multiple reaction monitoring [21].…”
Section: Introductionmentioning
confidence: 99%
“…Peptide retention time (RT) in a liquid chromatography tandem mass spectrometry (LC-MS/MS) experiment, i.e., the time points when peptides elute from the LC column as recorded by the instrument, is an intrinsic feature of a peptide. Recent studies have demonstrated the potential of predicting peptide RT on the basis of peptide sequence [26][27][28][29][30][31] . If the RT can be predicted with high accuracy for all peptides, the predicted RT of the peptide in each PSM can be compared with the observed RT associated with the spectrum to determine the quality of the PSMs.…”
mentioning
confidence: 99%
“…LsRP (Locus‐specific Retention Predictor) (http://elude.sbc.su.se/) allows for precise prediction of peptide retention time (RT), which is based on amino acid locus information and Support Vector Regression (SVR) algorithms . Indeed, LsRP provides a prediction correlation coefficient of 0.95∼0.99 and outperforms other methods and has tracked up to 30% extra peptides in an extraction RT window of two minutes, thus allowing further opportunities for precision proteomics.…”
Section: Data Preprocessing and Analysismentioning
confidence: 99%